TREATMENT EDUCATION OF LEXICAL AND GRAMMATICAL DISORDERS’S CONSTRUCTIONS IN PATIENTS WITH LOCAL BRAIN LESIONS (Proceedings of the World Disability & Rehabilitation Conference, 2019)
There is a need to form rehabilitation and correctional programmes for dyslexic people. This research aim is to study the problem of treatment of lexical and grammatical disorders’ formations in a daily care hospital treatment conditions. The speech function of patients with local brain lesions was analysed using method of dominant verbal functions’ evaluation (V.M. Schklovsky, T.G. Vizel). Treatment of disorders of lexical and grammatical constructions was deducted by the specially developed model of a treatment education in group and individual sessions with the use of different methods and assumptions chosen in accordance with the condition of the speech function of patients. The data analysis of the follow up speech function assessment after treatment education has revealed the significant improvement of the level of grammatical speech construction. Results of the research aimed to investigate the effectivity of the model of treatment of lexical and grammatical constructions in patients with local brain legions in a daily care hospital treatment has shown the positive dynamics of the treatment education as a result of the developed model of treatment.
Keywords: Aphasia; treatment education, expressive agrammatism; lexical and grammatical constructions